Dimensions of Humor Explorations in Linguistics, Literature, Cultural Studies and Translation - Varios autores (English In The World Series, 2011)
This is the first edited volume dedicated specifically to exploring humor in the academic world. It is a rich collection of essays by an international array of scholars representing various theoretical perspectives and practical orientations in the disciplines of Linguistics, Literature, Cultural Studies, and Translation, but all concerned with the interactional aspects of humor. The two main reasons behind the publication of this volume are, first, to continue the journey along the path towards full recognition of humor as a discipline worthy of research and assessment, and, second, to offer a new and integrating perspective on hu¬mor to showcase the wide range of dimensions that it offers. This book is sure to become an important reference and source of inspiration for scholars in the various subfields of Humor Studies: Linguistics, Literature, Cultural Studies, and Translation.@This is the first edited volume dedicated specifically to exploring humor in the academic world. It is a rich collection of essays by an international array of scholars representing various theoretical perspectives and practical orientations in the disciplines of Linguistics, Literature, Cultural Studies, and Translation, but all concerned with the interactional aspects of humor. The two main reasons behind the publication of this volume are, first, to continue the journey along the path towards full recognition of humor as a discipline worthy of research and assessment, and, second, to offer a new and integrating perspective on hu¬mor to showcase the wide range of dimensions that it offers. This book is sure to become an important reference and source of inspiration for scholars in the various subfields of Humor Studies: Linguistics, Literature, Cultural Studies, and Translation.